2021
DOI: 10.3389/fneur.2021.669567
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Reveals Longitudinal Changes in Retinal Damage Under Different Treatments for Neuromyelitis Optica Spectrum Disorder

Abstract: Background: Progressive retinal neuroaxonal damage after acute optic neuritis may occur in neuromyelitis optica spectrum disorder (NMOSD). However, it is unclear if treatments used to prevent attacks influence neurodegeneration.Objectives: We aimed to investigate retinal damage in patients treated with disease-modifying drugs in a longitudinal study.Methods: We retrospectively included 50 patients with aquaporin 4-antibody-seropositive NMOSD. Peripapillary retinal nerve fiber layer (pRNFL) thickness, macular g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Two observational studies with a retrospective before-after design were published in 2023 23 and 2021. 22 One study 23 retrospectively collected data for NMOSD patients treated with TCZ and compared the changes between baseline and after treatment. This study also employed adjusted logistic regression models to identify risk factors for relapse.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two observational studies with a retrospective before-after design were published in 2023 23 and 2021. 22 One study 23 retrospectively collected data for NMOSD patients treated with TCZ and compared the changes between baseline and after treatment. This study also employed adjusted logistic regression models to identify risk factors for relapse.…”
Section: Methodsmentioning
confidence: 99%
“…This study also employed adjusted logistic regression models to identify risk factors for relapse. The second study 22 included NMOSD patients treated with TCZ, AZA, and rituximab and healthy controls. This study compared the differences between baseline and after treatment within each treatment group or across the 3 drug groups as well as the difference between NMOSD patients and the healthy controls on optical coherence tomography (OCT) measures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GC-IPL damage on OCT spatial relationship and papillomacular bundle loss in neurodegenerative disease such as mitochondriopathy or neuroinflammmatory disease require further research to elucidate the damage in the megacellular and parvocellular layers in the lateral genicular nucleus [ 139 , 141 ]. There were no significant differences in the annual changes in mGC-IPL, pRNFL, total macular volume, and disc cup ratio in the NMOSD-ON eyes when comparing patients treated with different immunosuppressive therapies [ 142 ].…”
Section: Optic Nerve Structure In Nmosdmentioning
confidence: 99%
“…In addition, compared with steroids, tocilizumab treatment led to a significantly lower ARR and risk of relapse ( 54 ). A longitudinal study investigated retinal damage in 50 patients with NMOSD who received disease-modifying drugs and reported that, compared with AZA, tocilizumab and rituximab could delay macular ganglion cell complex thinning in the eyes of patients without a history of optic neuritis ( 55 ).…”
Section: Tocilizumabmentioning
confidence: 99%